Corneal calcification after amniotic membrane transplantation. Issue 5 (1st May 2003) - Anderson, S B; de Souza, R Ferreira; Hofmann-Rummelt, C; Seitz, B
Abstract : Background/aims: Amniotic membrane transplantation (AMT) has become well established as a treatment for chronic epithelial defects, conjunctival reconstruction, and partial limbal cell deficiency. The aim of this study was to describe cases of corneal calcification following AMT and to search for risk factors that might predispose to this unusual finding. Methods: Details of 117 AMTs on 93 corneas of 91 patients with a follow up period of at least 1 month performed since 1999 were collected prospectively. In those with calcification clinical photographs were studied and the medical records retrospectively examined. Results: 15 calcifications in 117 AMTs (12.8%) were identified, occurring 3–17 (median 6.1) weeks after AMT, during a follow up period of 4–151 (median 25) weeks. Overall epithelial healing rate was 83%. Calcification covered a surface area between 0.7–40.5 mm 2 maximum size with varied morphology. The primary diagnosis was diverse. Risk factors included the use of phosphate eye drops and pre-existing calcification in the operative or other eye. No patient with a "patch" AMT developed calcification. Conclusions: Corneal calcification occurs after some cases of AMT. A common risk factor was the postoperative use of phosphate containing eye drops.